2021
DOI: 10.4194/afs13
|View full text |Cite
|
Sign up to set email alerts
|

Fish Protein and Its Derivatives: Functionality, Biotechnology and Health Effects

Abstract: Animal derived proteins provide the essential amino acid requirements of a healthy diet. Among animal proteins, fish proteins have a well-balanced amino acid composition that are imperative for beneficial synthesizing and utilizing proteins in the body. Lack or low levels of any amino acid reduce the other amino acid utilization proportionately. This is why plant-derived proteins are potentially at a disadvantage for use in the body since they have relatively low levels of the essential amino acids methionine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…Milinsk et al [ 30 ] also reported a content of protein ranging from 9.50% to 12.56% FM in H. aspersa , a farmed snail fed a different feed formula. The protein content of C. saturnus was found to be lower than the levels found in conventional meats, including pork, beef, and chicken (17.3–24.1% FM) [ 31 ], and fish (15–20% FM) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Milinsk et al [ 30 ] also reported a content of protein ranging from 9.50% to 12.56% FM in H. aspersa , a farmed snail fed a different feed formula. The protein content of C. saturnus was found to be lower than the levels found in conventional meats, including pork, beef, and chicken (17.3–24.1% FM) [ 31 ], and fish (15–20% FM) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Temuan ini lebih tinggi dibandingkan dengan hasil penelitian yang dilakukan di Malaysia, Canakkale dan Istambul Turki dan dengan frekuensi konsumsi ikan masingmasing hanya 1 kali seminggu (Erdoǧan et al, 2011;Aziz et al, 2020;Saka & Bulut, 2020). Telah diketahui secara umum bahwa ikan merupakan salah satu sumber nutrisi, terutama protein yang bermanfaat bagi masyarakat selain telur dan susu (Alp Erbay & Yesilsu, 2021). Selain itu, jenis sumber protein ini juga dianggap paling ekonomis dan dapat dibeli dengan harga yang relatif murah oleh masyarakat (Mansoor & Jenkin, 2007).…”
Section: Hasil Dan Pembahasanunclassified
“…Karenanya, ikan laut merupakan salah satu sumber protein yang cukup populer dan cocok untuk semua kalangan baik dewasa maupun anak-anak. Selain itu, ikan laut sangat bermanfaat untuk pasien yang menderita peradangan, dalam proses penyembuhan luka (Lapi et al, 2021) dan juga sebagai diet penurunan berat badan untuk pasien obesitas (Alp Erbay & Yesilsu, 2021). Survei komparatif antara metode memasak yang berbeda untuk spesies ikan juga ditanyakan kepada responden.…”
Section: Hasil Dan Pembahasanunclassified
“…In terms of carbohydrates, fish contains no more than 0.3 % glycogen and 1–2% minerals, 0.5 % calcium, 0.25 % phosphorus and 0.1 % vitamins A, B, C and D in addition to their vitamins in fat [ 1 ]. Fish protein has a stable composition of essential amino acids with higher lysine and lower methionine and threonine content [ 2 ]. However, the meat yield and chemical composition of various fish vary.…”
Section: Introductionmentioning
confidence: 99%